From Reading Journal Articles to Research Synthesis: Pre-Service English Teachers' Development of Source-Based Academic Literacy - Fadhlan Saini; Ni Made Ratminingsih; Ni Luh Putu Sri Adnyani; Ni Luh Putu Eka Sulistia Dewi; Dewa Putu Ramendra (PT. Global Research Collaboration, 2026)
This study examines how pre-service English teachers develop source-based academic literacy as they move from reading journal articles to writing research syntheses. Framed by the Academic Literacies Model, it employed a qualitative descriptive design involving twelve eighth-semester students in an English Education Study Program in Indonesia. Data were collected through semi-structured interviews, reading and synthesis tasks, reflective journals, annotated articles, synthesis matrices, and students’ written work, and were analysed using reflexive thematic analysis. The findings show that development was gradual, recursive, and uneven. Students initially read journal articles for text-level comprehension, focusing on vocabulary, structure, and isolated meanings, but struggled to relate sources, transform summaries into synthesis, and construct an academic voice. This summary–synthesis gap was shaped by limited strategies, uncertainty about academic authority, and fear of misrepresenting authors’ ideas. Synthesis matrices, purposeful annotation, concept mapping, peer discussion, and reflection supported more analytical source use. The study contributes an explicit pedagogical explanation of how research synthesis can be systematically scaffolded in academic writing and research courses as both an academic literacy practice and a professional competence in English teacher education.